‘Women may preach but men must govern’: Gender Roles in the Growth and Development of the Bible Christian Denomination - Shorney, David (Studies in church history, 1998)
When the Cornish lay evangelist, William O’Bryan, founded the first Bible Christian societies in the late autumn of 1815 he was responding, in the main, to female initiatives. This is not altogether surprising. For several decades before 1815 women had been playing a much larger role in English evangelical Christianity than they had done in the early years of the Evangelical Revival. The informal groupings which came into existence in its second phase, c. 1790-c. 1830, gave women opportunities to initiate, organize, and exhort on a much more extensive scale. As cottages and farmsteads became centres of worship, women were well placed to play a more important role as initiators and organizers, especially in those areas barely affected by John Wesley, George Whitefield, and their travelling preachers. The more articulate went even further and followed the example of some eighteenth-century Quaker women by speaking in their own localities and further afield. Before the eighteenth century came to an end a number had acquired the reputation of being gifted preachers and ‘holy women’, ‘owned by God’, and called to instruct others, both men and women, in the Christian faith. For a short while women were poised in Wesleyan, and later, Primitive Methodism to play a major role in evangelism and church-planting; but it was only amongst the Bible Christians that they, for a time, played perhaps an even more significant role as evangelists than their male colleagues. As such they were in no way inferior to men; but when the denomination acquired a governmental structure copied from Wesleyan Methodism the patriarchal ordering of contemporary society set limits to their Bible-based notions of sexual equality.